The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 IEEE 15th International Symposium on Biomedical Imaging (ISBI 2018) 2018
DOI: 10.1109/isbi.2018.8363618
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level convolutional LSTM model for the segmentation of left ventricle myocardium in infarcted porcine cine MR images

Abstract: Automatic segmentation of left ventricle (LV) myocardium in cardiac short-axis cine MR images acquired on subjects with myocardial infarction is a challenging task, mainly because of the various types of image inhomogeneity caused by the infarctions. Among the approaches proposed to automate the LV myocardium segmentation task, methods based upon deep convolutional neural networks (CNN) have demonstrated their exceptional accuracy and robustness in recent years. However, most of the CNN-based approaches treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Previously, Avendi et al used the CNN to automatically detect the left ventricle chamber in an MRI data set . In addition, Zhang et al combined recurrent neural network with convolutional LSTM for left‐ventricle myocardium segmentation . Xue et al introduced a spatial–temporal circle LSTM model to calculate left‐ventricle myocardial thickness in the short axis scan …”
Section: Discussionmentioning
confidence: 99%
“…Previously, Avendi et al used the CNN to automatically detect the left ventricle chamber in an MRI data set . In addition, Zhang et al combined recurrent neural network with convolutional LSTM for left‐ventricle myocardium segmentation . Xue et al introduced a spatial–temporal circle LSTM model to calculate left‐ventricle myocardial thickness in the short axis scan …”
Section: Discussionmentioning
confidence: 99%
“…Long short-term memory (LSTM) is a popular RNN [ 37 ] technique for detecting heart motion using spatiotemporal dynamics. Zhang et al [ 38 ] created a multi-level LSTM model for LV segmentation that used low-resolution level features to train one model and high-resolution level features to train another. Additionally, due to the large slice thickness, Baumgartner et al [ 39 ] found that segmentation by 2D CNN performed better than 3D CNN.…”
Section: Related Workmentioning
confidence: 99%
“…The combination of 2D and temporal information compensates the loss of the original data spatial structure of the 2D convolution network by using a time storage network such as long short-term memory (LSTM). Zhang et al [15] proposed a multi-level convolutional long short-term memory (ConvLSTM) model to the segmentation of left ventricle myocardium. LSTM is often used in time series data.…”
Section: E Combining 2d and Temporal Informationmentioning
confidence: 99%